Promoting financial capability within the field of social work practice among families with children: a systematic review = Taloudellisen toimintakyvyn edistäminen lapsiperheiden parissa tehtävässä sosiaalityössä: systemaattinen kirjallisuuskatsaus - Viitasalo Katri; Kaitsaari Tuula; Kaittila Anniina; Moisio Meri; Hakovirta Mia (Routledge Journals, Taylor & Francis Ltd, 2025)
Financial difficulties have a severe impact on families and children who grow up in poor families. Social workers can help families address their financial problems through a variety of practice settings, hence simultaneously promoting financial well-being. We investigate how financial capability among families with children has been promoted in social work practice. We generated a systematic review by following the PRISMA standards and applying the concepts of the CAIMeR theory. Two hundred seventy-seven references were identified, of which a total of 14 articles were analysed. We found there was a large understanding about the phenomenon, but the knowledge of contexts was limited, with a lack of evidence-based knowledge. Formal interventions in social work practice emphasise financial education as a key contributor to financial capability. Likewise, the improvement of financial inclusion is underlined. The literature indicates that interventions provide tools for clients to help strengthen economic self-sufficiency and increase financial confidence. However, social work practices often concentrate on money management, ignoring the ways in which clients can increase income and other resources or avoid future risks. Implementation of interventions requires attention. Unique situations in the family should be considered closely, and the implementation should rely more consciously on the psychosocial elements of support.